Advances in immunoPET/SPECT imaging: The role of Fab and F(ab′)2 fragments in theranostics - Wenpeng Huang; Jingwei Zhou; Yanchen Liu; Yihan Yang; Rachel J. Saladin; Jessica C. Hsu; Weibo Cai; Lei Kang (Acta Pharmaceutica Sinica B)
With the advent of precision medicine and personalized treatment, targeted therapies have become pivotal in oncology. Noninvasive molecular imaging, especially immunoPET/SPECT, plays a crucial role in refining cancer diagnostics and treatment monitoring by visualizing biological processes at the molecular level. This review explores the dynamic field of immunoPET/SPECT imaging using Fab and F(ab′)2 fragments, characterized by advantageous pharmacokinetics and swift clearance from the bloodstream, making them suitable for same-day imaging procedures. We examine contemporary strategies for radiolabeling these fragments with PET and SPECT radionuclides and discuss potential advancements and the challenges anticipated in the further development of Fab and F(ab′)2 fragments. Despite the complexities involved in their development, these fragments hold significant promise for advanceing personalized cancer treatment. Keys to this advancement are innovative radiolabeling techniques, site-specific conjugation chemistries, and short-lived radionuclides, all of which are crucial for overcoming existing limitations and enhancing the clinical utility of these imaging agents. As research progresses, Fab and F(ab′)2 fragments are expected to become central to the future of cancer diagnostics and therapeutic monitoring, thereby improving patient management and contributing significantly to the evolution of personalized medicine.